Regional features of birth rate and mortality in the North Caucasus region in the famine of 1932–1933 years - Nazar N. Nazarenko; Anatoliy V. Bashkin (Кавказология, 2022)
The article reviews the vital statistics analysis during the 1932–1933 famine in the North Caucasus region. It has been established that vital statistics registration high level and full population cover occurred in Don, Kuban’ and Stavropol’ regions high underestimating of rural population occurred in highlands national autonomies. The non-local and unknown identity residents’ birth rate and mortality are registered in Dagestan, but for other regions, the registration of non-local and unknown identity residents and presence of these data in vital statistics has not ascertained. The estimation of birth rate and mortality has done for North Caucasus by regions with underestimating correction. It has been shown that characteristic famine peak occurred in 1933 year spring in Don, Kuban’ and Stavropol’ regions at the same time and almost equally. The most high mortality of rural population was in Stavropol’ region, regions of Kuban’ and southern Don were losses rather fewer and fewer losses regions of north Don. It has been detected the regions of catastrophic mortality and catastrophic of natural loss of population. The natural increase of rural population was in highlands national autonomies and Black Sea seaside regions of Kuban. It has been ascertained, that urban population mortality of North Caucasus was not low mortality than country. It has been shown the demographic catastrophe in North Caucasus cities and towns, which disprove sociocide of country people (Cossacks) hypothesis in examined region during the 1932–1933 famine. It has been demonstrated absence of ethnocide (genocide) in North Caucasus regions and famine artificiality by common plan and central authority organization. The mortality in North Caucasus had zonal allocation and was determined by local government response, natural, climate and epidemics conditions and administrative borders most likely. The total demographic losses due to decreased birth rate in North Caucasus regions in 1932–1934 came to 190000 persons and entire number of excess deaths – 280000 persons.